(untitled) (Journal of the Bangladesh Agricultural University, 2020)
The river-water of Dhaka city is polluting day by day because of increasing level of industrialization, poor water use practice and wastewater management inefficiency. Heavy metals present in riverwater are uptaken by food crops when it is used as irrigation purposes which ultimately causing health risks. A pot experiment was conducted to assess the extent of pollution of four rivers water surrounding Dhaka city and to evaluate their effects on the yield and heavy metal concentrations and their uptake by rice and cabbage. Ten water samples of each river viz., Buriganga, Shitalakshya, Turag and Bangshi were collected and analyzed. Crop growth experiment was laid out following completely randomized design with three replicates. The pH, electrical conductivity (EC), total dissolved solids (TDS) and dissolved oxygen (DO) ranged from 5.45 to 7.60, 170 to 1374 (μS cm-1), 451 to 1827 (mg L-1) and 1.8 to 6.5 (mg L-1), respectively. The highest Pb (72.5 mg L-1), Zn (675.8 mg L-1) and Cd (1.08 mg L-1) concentrations were found in Buriganga water whereas the highest Cr concentration (95.2 mg L-1) was found in the water of Turag river. The concentrations of the heavy metals in those rivers were above the permissible limit with the exception of Shitalakshya riverwater. In terms of heavy metal pollution, water of four rivers were of the following order: Buriganga > Turag > Bangshi > Shitalakshya. River-water irrigation reduced the yield up to 27% for rice and 38% for cabbage compared to freshwater. The lowest yield of rice and cabbage (3.2 and 25.3 t ha-1, respectively) was found with Buriganga river-water irrigation. The highest Pb (3.72 mg kg−1), Cd (0.08 mg kg−1) and Zn (8.90 mg kg−1) concentrations in rice grain were recorded in the plants grown with Buriganga river-water, whereas the highest Cr concentration (2.34 mg kg−1) was obtained from Turag river-water irrigated rice plant. In cabbage, the highest concentrations of Pb, Cd and Zn were 4.38, 0.012 and 8.86 mg kg−1, respectively recorded from the irrigation of Buriganga river-water, whereas the highest Cr concentration (3.02 mg kg−1) was recorded from Turag river-water irrigation. The overall results suggested that the studied river-water may not be used directly without proper treatment for rice and cabbage production. J Bangladesh Agril Univ 18(2): 332–339, 2020 https://doi.org/10.5455/JBAU.81603